Cinnamomum Burmannii (Nees & T. Nees) Blume: A Global Evidence Review F Phytochemistry, Preclinical Pharmacology, Clinical Investigations, and Standardised Bioactive Fractions - Raymond R. Tjandrawinata (Syntax Corporation Indonesia, 2025)
Cinnamomum burmannii (Nees & T. Nees) Blume is one of the most widely traded cinnamon species globally and an increasingly investigated botanical source for metabolic, antimicrobial, anti-inflammatory, dermatological, and gastroprotective applications. Cultivated predominantly in Indonesia and distributed across tropical Southeast Asia and southern China, C. burmannii is distinguished by its high coumarin content, chemically rich and variable phytochemistry—dominated by cinnamaldehyde, A-type proanthocyanidins, D-borneol-rich essential oil, and phenolic acids—and by the emergence of standardized bioactive fractions with clinical development. This review integrates the totality of published evidence across two parallel research streams: a broad international body of phytochemical and pharmacological work from Indonesian, Chinese, Belgian, Portuguese, and other research groups, and a focused translational program from Dexa Laboratories of Biomolecular Sciences (DLBS), comprising DLBS3233—a combined C. burmannii/Lagerstroemia speciosa fraction supported by multiple Phase II–III randomized controlled trials in prediabetes, type 2 diabetes mellitus, and polycystic ovary syndrome—and DLBS2411, a bark-derived proton pump downregulator and mucoprotector with clinical trials in GERD, peptic ulcer, and functional dyspepsia. The collective evidence demonstrates robust antidiabetic activity via α-glucosidase inhibition, insulin receptor phosphorylation, PPARγ/GLUT4 upregulation, and TRPA1/GLP-1 stimulation; antioxidant and antilipidemic effects across multiple animal and human models; broad-spectrum antimicrobial activity against foodborne pathogens, Staphylococcus aureus, Aspergillus flavus, and Malassezia furfur, with characterized molecular mechanisms; anti-inflammatory action through NF-κB/IKK suppression; wound-healing promotion via M1 macrophage inhibition; and gastroprotective dual-mechanism activity.